1988
DOI: 10.1002/etc.5620070906
|View full text |Cite
|
Sign up to set email alerts
|

Attached‐algal abundance altered by individual and combined treatments of zinc and pH

Abstract: Attached‐algal communities were employed to test the U.S. Environmental Protection Agency's (EPA) guidelines for zinc (Zn) and pH. The EPA criterion for Zn is 0.047 mg/L, and the EPA effluent standard generally requires that discharge water fall between pH 6 and 9. The experiment was designed to determine whether algal community composition and abundance would be altered by (a) pH 6 or 9, (b) 0.05 mg/L Zn, or (c) the combination of pH 6 or 9 and 0.05 mg/L Zn. Stream mesocosms were continuously supplied with na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…For example, Genter et al [53] found snail and zinc treatment to alter periphytic biomass and community structure. Others found zinc treatment of 50 μg/L to reduce diatom abundance and increase dominance of green algae in periphytic communities [54]. Increased biomass but not primary productivity may have resulted if tolerant but less productive green algae contributed to our biomass measures.…”
Section: Discussionmentioning
confidence: 92%
“…For example, Genter et al [53] found snail and zinc treatment to alter periphytic biomass and community structure. Others found zinc treatment of 50 μg/L to reduce diatom abundance and increase dominance of green algae in periphytic communities [54]. Increased biomass but not primary productivity may have resulted if tolerant but less productive green algae contributed to our biomass measures.…”
Section: Discussionmentioning
confidence: 92%
“…A widely distributed diatom, A. minutissimum is sensitive to organic (biochemical oxygen demand or saprobic) pollution [34] yet tolerant to at least some metals [17]. The patchy distribution of this taxon is not strong evidence to support the hypothesis that it occurs because of metal stress, but this spatial variation has been observed previously [11,13,14,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…A widely distributed diatom, A. minutissimum is sensitive to organic (biochemical oxygen demand or saprobic) pollution [34] yet tolerant to at least some metals [17]. The patchy distribution of this taxon is not strong evidence to support the hypothesis that it occurs because of metal stress, but this spatial variation has been observed previously [11,13,14,40,41].…”
Section: Algaementioning
confidence: 94%